Media Ular Tangga Numerasi untuk Meningkatkan Motivasi Siswa Terhadap Pembelajaran Matematika Kelas IV SD Negeri Tegalsari - Siswanti, Feliyana (Papanda Publisher, 2025)
Numeracy is the ability to apply number concepts, calculation operation skills, and the ability to explain numeracy information in everyday life. At the elementary school level, math numeracy is often considered a difficult and boring subject for students, resulting in a decrease in their learning achievement. The low learning achievement of students is one of the causes of the lack of student motivation. The purpose of this research is to assist students in increasing motivation towards numeracy learning by providing creative media implementation in the form of numeracy snakes and ladders learning media. The method used in this research is descriptive qualitative with data collection through observation, interviews, and documentation. The results of this study are students become more understanding of the material, the implementation of learning becomes fun, learning activities become interactive, and students' numerical learning motivation increases. Therefore, snakes and ladders learning media can increase the learning motivation of elementary school students in mathematics. Kemampuan numerasi merupakan kemampuan yang menerapkan konsep bilangan, keterampilan operasi hitung, dan kemampuan menjelaskan informasi numerasi dalam kehidupan sehari-hari. Pada tingkat sekolah dasar, numerasi matematika sering dianggap sebagai mata pelajaran yang sulit dan membosankan bagi siswa, sehingga berdampak pada menurunnya prestasi belajar mereka. Rendahnya prestasi belajar siswa merupakan salah satu penyebab dari kurangnya motivasi belajar siswa. Tujuan dari penelitian ini ialah untuk membantu siswa dalam meningkatkan motivasi terhadap pembelajaran numerasi dengan memberikan implementasi media yang kreatif dalam bentuk media pembelajaran ular tangga numerasi. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif dengan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Adapun hasil dari penelitian ini adalah siswa menjadi lebih memahami materi, pelaksanaan pembelajaran menjadi menyenangkan, kegiatan belajar menjadi interaktif, dan motivasi belajar numerik siswa menjadi meningkat. Maka dari itu, media pembelajaran ular tangga mampu meningkatkan motivasi belajar Matematika siswa sekolah dasar.